Adaptive control method for functional simulators - Синєглазов, В.М.; Борсук, С.П. (Proceedings of National Aviation University (archive), 2008)
The structural scheme of operators studying process control and management in the training complex is proposed for observation. Structural scheme includes the division of operators upon the subgroups according to the level of demonstrated knowledge. Also in the article the example of such divisions criteria is presented.